Academic Research on Indian Mutual Funds : A Systematic Review - Mohan, Aditi; Bohra, N. S. (Indian Journal of Finance, 2023)
Purpose : This study presented a systematic review of academic research conducted on the Indian mutual fund industry (IMFI). Our objective of this review was to present the academic researchers’ perspectives on the fastest-growing preferred investment avenue of the Indian financial system. Design/Methodology/Approach : The study adopted a systematic review approach and selected two verticals of academic research; the first one in the form of doctoral dissertations, and the other is the research articles published in academic journals. Doctoral dissertations between 2000 – 2022 were extracted from Shodhganga (the digital repository of the University Grants Commission), and research articles were extracted from the Scopus database. Findings : A comprehensive review conclusion was drawn from this study, which concluded that the IMFI is growing exponentially in T30 and B30 cities (T30 and B30 cities are geographical segmentations made by SEBI and AMFI based on AUM, T30 means top 30 Indian cities contributing maximum AUM and B30 are beyond T30 cities). We reviewed 374 doctoral dissertations for this study; 83 dissertations were submitted during the first decade of the 20th century. State-level universities have produced a higher number of dissertations than central and deemed universities. Based on the dissertations’ titles, we classified dissertations into four categories of themes. The first theme is the marketing mechanism used by mutual funds to promote their mutual fund schemes, where we found the minimum number of theses; the comparative study is the second theme; here, we found that the comparison was made at various levels. The third and most interesting theme is investors’ perspectives on mutual fund investments. The maximum number of doctoral dissertations was carried out on the theme of performance evaluation. In the second vertical, we extracted 69 research articles published in 13 journals, and finally, 10 articles with a minimum of five citations were reviewed. We found no correlation between the research papers published in the Scopus database to the completed dissertations. Practical Implications : The probable stakeholders of this study are future academic researchers in the same field. For them, this study is a systematic framework that can provide a basis for future research gap analysis. Academic institutions are another stakeholder ; the important stakeholder is IMFI, where institutional policymakers can formulate strategies for their future mutual fund schemes.